The Character-Based Islamic Religious Education Management For The Blind in LKSA Blind ' Aisyiyah Ponorogo - Muqorrobin, Syamsul (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study aims to explore and analyze the management of character-based Islamic religious education for blind children in the Integrated Blindness LKSA ‘Aisyiyah Ponorogo. This study uses a qualitative phenomenological approach to understand the experiences of blind children receiving character-based Islamic education at LKSA Tunanetra Terpadu ‘Aisyiyah Ponorogo. The research explores how these children perceive and experience Islamic character formation, with data gathered through in-depth interviews, participant observation, and documentation. Data analysis involves reduction, categorization, and theme identification to highlight key themes such as spiritual closeness, discipline, and empathy. Triangulation and member-checking are applied to ensure data validity, aiming to capture the comprehensive meaning of religious education in the children’s lives. The character-based Islamic education at LKSA Tunanetra Terpadu 'Aisyiyah Ponorogo is essential in fostering moral, spiritual, and social growth in blind children. Its tailored curriculum helps children internalize Islamic values for future guidance. Programs like muhadhoroh, tahfidz, and routine prayers allow them to learn Islamic teachings while using adaptive tools like Braille, audio, and tactile methods. These approaches bridge their visual limitations and provide a comprehensive learning experience. Overall, the institution plays a vital role in equipping children with values that shape their personal development.